2019
DOI: 10.1111/den.13541
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of underwater endoscopic mucosal resection and management of residues for superficial non‐ampullary duodenal epithelial neoplasms

Abstract: Background and Aim: Underwater endoscopic mucosal resection (UEMR) is effective for superficial non-ampullary duodenal epithelial neoplasms (SNADEN). However, the incidence of residual lesion after UEMR, especially for large lesions (≥20 mm), and their prognosis remain unclear. We aimed to assess the incidence of residual lesions and further outcomes after UEMR for SNADEN. Methods:We carried out a retrospective study at a tertiary cancer institute. Candidates for the study were systematically retrieved from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 23 publications
5
45
0
Order By: Relevance
“…Advanced duodenal cancer has a poor prognosis 7 ; therefore, early detection is required. Favorable short‐term and long‐term outcomes of endoscopic treatment at early stages were reported in Japan 19–24 . Our study results indicated that conducting screenings in individuals aged <80 years would contribute to the early detection of this disease and an improvement in its prognosis.…”
Section: Discussionmentioning
confidence: 55%
“…Advanced duodenal cancer has a poor prognosis 7 ; therefore, early detection is required. Favorable short‐term and long‐term outcomes of endoscopic treatment at early stages were reported in Japan 19–24 . Our study results indicated that conducting screenings in individuals aged <80 years would contribute to the early detection of this disease and an improvement in its prognosis.…”
Section: Discussionmentioning
confidence: 55%
“…Our case series suggested the potential of UEMR for the treatment of neoplasms located in the pyloric ring. UEMR, with a relative short procedure time and low rate of adverse events, does not require high technical skills in endoscopic procedures[ 6 ]. UEMR for the management of neoplasms in the pyloric ring has benefits similar to those of UEMR for colorectal neoplasms: (1) Superficial lesions float into the snare as protruding lesions in underwater conditions; (2) UEMR decreases the thermal damage to the gastrointestinal wall, which helps prevent delayed perforation; and (3) The resection plane in UEMR is superficial; thus, the submucosal vessels usually remain within the resection wound, whereas in conventional EMR, the submucosal vessels are disrupted[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, underwater endoscopic mucosal resection (UEMR) was suggested by Binmoeller et al[ 1 ], which has been used in the treatment of challenging lesions in the duodenum and colorectum near the appendiceal orifice and dentate line; UEMR has shown good treatment results with a high complete resection rate and low adverse event rate[ 2 - 5 ]. UEMR has also been adapted for recurrent or residual lesions after endoscopic resection[ 6 , 7 ]. Here, we reported our experience of using UEMR for benign mucosal neoplasms located in the pyloric ring.…”
Section: Introductionmentioning
confidence: 99%
“…Underwater endoscopic mucosal resection (UEMR) is reportedly efficacious and safe to remove colorectal and duodenal polyps, including intra‐mucosal cancers 1–5 . However, information on UEMR in the terminal ileum is lacking.…”
Section: Brief Explanationmentioning
confidence: 99%